WHEN SUPPORT MATTERS: MODERATING EFFECTS OF PERCEIVED ORGANIZATIONAL SUPPORT ON WORK-LIFE BALANCE, JOB ENVIRONMENT, AND PERFORMANCE - Lestari, Nurul Sukma; Aphrodya, Cerry; Nur Afini, Dinar; Yulianti, Jessyca; Assadiyah, Dinda Emily; Triana, Ika (International Humanities and Applied Science Journal, 2025)
This study investigates the effects of work-life balance and the workplace environment on job performance, with perceived organizational support (POS) serving as a moderating variable. The study addresses a research gap by focusing on staff members at locally branded five-star hotels in Jakarta and integrates these variables into a single model within a local organizational framework. A quantitative approach was employed using a standardized online questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the data, and bootstrapping was used for moderation analysis. The findings show that job environment and work-life balance significantly impact job performance. Furthermore, the association between work environment and job performance is strongly moderated by POS, but not between work-life balance and job performance. These findings suggest that organizational support has a contextual influence and is more effective at improving job performance through working conditions than through personal balance variables.  The study contributes to the literature by exploring how internal and perceived external factors influence employee performance, particularly within locally branded hotel settings